2015
DOI: 10.2169/internalmedicine.54.4091
|View full text |Cite
|
Sign up to set email alerts
|

Primary Squamous Cell Carcinoma of the Pancreas: A Report of Two Cases and Review of the Literature

Abstract: Primary squamous cell carcinoma (SCC) of the pancreas is extremely rare. We herein report two such cases. Aside from various morphological characteristics, the clinical presentation of pancreatic SCC is the same as that of adenocarcinoma. The treatment is controversial, and the prognosis is poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…Our study excluded mixed adenosquamous histological subtype resulting in a more homogeneous study population of patients diagnosed with pure squamous histology. In absence of population-based studies for SCC the evidence for SCC survival comes from case series reports 9,11,36-39 . The case series studies for patients with SCC reported median survival of 3 months 38 in patients treated with palliative intent and survival of 7 months 9 in patients who received potentially curative surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study excluded mixed adenosquamous histological subtype resulting in a more homogeneous study population of patients diagnosed with pure squamous histology. In absence of population-based studies for SCC the evidence for SCC survival comes from case series reports 9,11,36-39 . The case series studies for patients with SCC reported median survival of 3 months 38 in patients treated with palliative intent and survival of 7 months 9 in patients who received potentially curative surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The available published data on squamous subtype of pancreatic cancer is very limited, mostly presented as individual case reports or small case series studies. 5-11 As a result, the epidemiology and clinical course of pure squamous cell pancreatic carcinoma remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, parenchymal squamous metaplasia is commonly detected in pancreatic specimens, and can be detected in 17% to 48% of cases [4]. Despite the relatively high frequency of squamous metaplasia, pancreatic squamous cell carcinoma (SCC) is a rare primary pancreatic malignancy, accounting for 0.05–5% of all pancreatic cancers approximately [4, 16–20]. In the present study, we screened 1033 cases of pancreatic cancer in Chinese population, and identified only 2 cases of pure SCC, accounting for only 0.19% of all cases.…”
Section: Discussionmentioning
confidence: 99%
“…By now, there are only twenty reported cases of pancreatic SCC (Table 7) [5, 1416, 18, 19, 21, 2435], providing limited, but valuable clinical information. The clinical presentation of SCC is similar to that of AC.…”
Section: Discussionmentioning
confidence: 99%